Women's Leadership in the Indonesian Context: From Interpretative Discourse to Contemporary Fiqh Siyasah - Mutho'am Mutho'am; Heriyanto Heriyanto (MUWAZAH : jurnal kajian gender, 2023)
This article aims to explore women's leadership within the Indonesian context, focusing on contemporary discourse on interpretation and fiqh siyasah. This study seeks to understand how the dynamics of thought and the interpretation of religious texts in Indonesia relate to the position of women in the political sphere. The research employs a qualitative approach using text analysis and discourse analysis. Data is collected from various sources, including relevant literature, policy documents, and the experiences of female leaders involved in leadership roles. This methodology is designed to uncover diverse perspectives on women's leadership and how interpretations of tafsir and fiqh siyasah can be applied in a modern context. The findings of the research indicate that although traditional interpretations of Islamic texts often limit women's roles in leadership, contemporary movements and reinterpretations of fiqh siyasah are challenging these norms. The study identifies significant barriers to women's leadership, including socio-cultural attitudes and institutional biases. It concludes that changes in mindset and policy are crucial for fostering an inclusive political environment that recognizes and promotes women's leadership. Thus, the progressive reinterpretation of religious texts and the development of a more inclusive contemporary fiqh siyasah regarding women's leadership is essential to ensure that women's contributions to politics are grounded in a strong legal religious standing